Effects of territorial and worldwide corporation tax systems on outbound M&As - Lars P. Feld; Martin Ruf; Uwe Scheuering; Ulrich Schreiber; Johannes Voget (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
Repatriation taxes reduce the competitiveness of multinational firms from tax credit countries when bidding for targets in low tax countries. This comparative disadvantage with respect to bidders from exemption countries violates ownership neutrality, which results in production inefficiencies due to second-best ownership structures. This paper empirically estimates the magnitude of these effects. The abolishment of repatriation taxes in Japan and in the U.K. in 2009 has increased the number of acquisitions abroad by Japanese and British firms by 31.9% and 3.9 %, respectively. A similar policy switch in the U.S. is simulated to increase the number of U.S. cross-border acquisition by 17.1 %. We estimate the yearly gain in efficiency to be around 525 million dollar due to the Japanese reform and 13.5 million dollar due to the U.K. reform. Simulating such a reform for the U.S. results in a yearly efficiency gain of 1134 million dollar.
urn:nbn:de:bsz:180-madoc-352166
Keywords: H25; F23; G34; 330; international taxation; ownership neutrality; cross-border M&As; repatriation taxes